2023
DOI: 10.1111/apt.17755
|View full text |Cite
|
Sign up to set email alerts
|

Open‐label, clinical trial extension: Two‐year safety and efficacy results of seladelpar in patients with primary biliary cholangitis

Marlyn J. Mayo,
John M. Vierling,
Christopher L. Bowlus
et al.

Abstract: SummaryBackgroundSeladelpar is a potent and selective peroxisome proliferator‐activated receptor‐δ agonist that targets multiple cell types involved in primary biliary cholangitis (PBC), leading to anti‐cholestatic, anti‐inflammatory and anti‐pruritic effects.AimsTo evaluate the long‐term safety and efficacy of seladelpar in patients with PBC.MethodsIn an open‐label, international, long‐term extension study, patients with PBC completing seladelpar lead‐in studies continued treatment. Seladelpar was taken orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Mayo et al 7 have reported the 2‐year safety and efficacy results of an open‐label LTSE study with seladelpar in subjects with PBC who completed 1 year in phase 2 ( n = 104) and phase 3, ENHANCE study ( n = 2) 8,9 . Although 106 subjects were enrolled, only 53 completed 2 years in the study: 79% achieved the composite endpoint (ALP < 1.67 × ULN, >/=15% ALP decrease and normal total bilirubin) with 40% achieving ALP normalisation.…”
Section: Figurementioning
confidence: 99%
“…Mayo et al 7 have reported the 2‐year safety and efficacy results of an open‐label LTSE study with seladelpar in subjects with PBC who completed 1 year in phase 2 ( n = 104) and phase 3, ENHANCE study ( n = 2) 8,9 . Although 106 subjects were enrolled, only 53 completed 2 years in the study: 79% achieved the composite endpoint (ALP < 1.67 × ULN, >/=15% ALP decrease and normal total bilirubin) with 40% achieving ALP normalisation.…”
Section: Figurementioning
confidence: 99%
“…Other PPAR ligands such as seladelpar (MBX-8025), elafibranor (GFT-505), and saroglitazar are also currently undergoing investigation. Seladelpar is a selective PPARδ agonist, with reported safety and efficacy in improving liver biochemical response and alleviating pruritus in PBC patients [81][82][83][84]. In a recently published phase 3 clinical trial, seladelpar demonstrated significant improvements compared to placebo in terms of biochemical response, normalization of alkaline phosphatase, and alleviation of itching [111].…”
Section: Ppar Agonistsmentioning
confidence: 99%
“… 99 After 24 months of treatment, the number of patients responding to seladelpar increased from 66% to 79% and the number of patients with normalization of ALP levels increased from 26% to 42%. 100 Seladelpar relieves itching and lowers bile acid and IL-31 levels. 101 Seladelpar at a dose of 5/10 mg also improves sleep and fatigue in patients with PBC.…”
Section: Perspectives On the Treatment Of Pbcmentioning
confidence: 99%